Explaining variance in self-efficacy among adolescents: the association between mastery experiences, social support, and self-efficacy - Annette Løvheim Kleppang; Anne Mari Steigen; Hanne Søberg Finbråten (BMC, 2023)
Abstract Background Self-efficacy has been identified as an important health-promoting factor for both physical and mental health. Previous studies have examined self-efficacy as a moderating factor between negative psychosocial influences and various outcomes, e.g., life satisfaction and stressors. There is, however, limited knowledge about factors that strengthen self-efficacy. The aim of this study is to examine the association between mastery experiences, social support, and self-efficacy among adolescents in secondary schools in Norway. Methods This study is based on cross-sectional data from the Ungdata surveys conducted in eastern part of Norway in 2021. The sample comprises 9,221 adolescents aged 13-16. Sequential multivariate linear regression was conducted to explore the association between mastery experiences, social support, and self-efficacy. Results The final model (Model 3) explains 25% of the total variance in self-efficacy. The indicators concerning mastery experiences - defined here as the personal experience of success - explain more of the observed variance in self-efficacy than the other independent variables (change in R square = 10.7%). The items 'felt mastering things' 'and 'felt useful' make the strongest and most significant contributions to the variance in self-efficacy in the final model (β = 0.25, p < 0.001 and β = 0.16, p < 0.001, respectively), followed by the variables 'support from friends' and 'parental support' (β = 0.06, p < 0.001 an β = 0.06, p < 0.001). Conclusions Mastery experiences are potential sources for creating and strengthening self-efficacy. Awareness of the health-promoting potential in (strengthening) self-efficacy among adolescents is important. Additional research is needed to further explore these associations.